Managing the Regulatory Environment : Best Practices. - Association, American Dental (Guidelines for Practice Success Ser., 2017)
Provides an overview of the federal regulations from the DEA, CDC, OSHA, HIPAA, EPA and ACA-1557 that impact the dental office. Includes quick overviews, checklists, do's and don'ts, tip sheets and FAQ on how to comply with the most common regualtions that impact a dental practice.